Antiproliferative and Erythroid Differentiation Activities of Cedrus libani Seed Extracts against K562 Human Chronic Myelogenus Leukemia Cells - Guerrini, Alessandra (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Seeds of C. libani have been extracted through ultrasound-assisted maceration and evaluated in order to check their antiproliferative and erythroid differentiation properties. Preliminary chemical compositions of the extracts have been also performed with the object to identify the chemical classes mainly responsible of the bioactivity. Chloroform and ethanol extracts were tested for growth inhibition and erythroid differentiation induction in K562 cells. Both the extracts were then analysed by GC and GC-MS. Chloroform extracts evidenced the predominant presence of terpenes, the monoterpenes α- and β-pinene checked as the most abundant (34.42±1.22 % and 33.28±1.08 % respectively), and most probably directly involved in the antiproliferative activity against K562 cells (IC50=69.20±1.69 µg/ml). Ethanol extracts evidenced a slightly higher antiproliferative activity (IC50=40.57±1.16 µg/ml) which could be mainly related to abietane diterpenoids and to the less abundant palmitic acid (0.53±0.03 %) and methyl linoleate (1.43±0.12 %). Erythroid differentiation assays showed the better performance of ethanol extracts (16.00±1.52 % at 10 µg/ml), with respect to that lower of chloroform ones (12.00 ±1.25 % at 50 µg/ml). This first report about C. libani seed extracts sheds a light both on the health importance of this lebanese plant specie and, in particular, on natural compounds researches for treatments of human blood related diseases.